(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Grimmia crinita Bridis reported from Kazantipsky Nature Reserve’s limestones as a new spesies for moss flora of Ukraine. The special description and a key for Ukrainian Grimmia with capsule immersed is given.